Desenvolvimento de um sistema para avaliação de desempenho de usuários de cadeira de rodas motorizada - Silva, Daniela de Cássia (2020)
Physical disability affects a gigantic number worldwide and can bring several limitations. Assistive Technology (TA) is a resource and tool developed for these people, to recover lost and impaired functions. The powered wheelchair (PW) is a very well-known and used AT, due to the low energy expenditure and to assist people with different types and degrees of motor disabilities. However, the act of driving it is not as simple as it seems. Nowadays, research on CRM training is investigated, which aims to reduce driving difficulties and several other barriers faced by wheelchair users, aiming to promote confidence, independence, and a better life quality. The health professionals responsible for this training make use of different support tools. However, there are still no quantitative measures for assessing wheelchair users, during training, in real and real-time. Thus, there is a great interest in seeking methods that facilitate the assessment of the performance and learning of the PW user, which is not based only on the observation and opinion of the responsible professional. Currently, there are ways to evaluate these PW users in virtual and real environments, with only one metric, being command or elapsed time to complete a route. Thus, the objective of this study is to design a portable system capable of recording three user performance metrics during their training in driving a PW, which are: number of commands, time, and number of collisions. An equipment developed transmit all these data using Bluetooth protocol to the software responsible to monitor the user's performance in real-time. The equipment showed efficient results in the performed tests and the methodology used for communication and presentation of the data was satisfactory. Thus, it is possible to follow the evolution of the CRM user during the training and save the data related to the session. After, it is possible to verify and compare the users performance in several sessions, demonstrating to be a viable instrument for tests in clinical practice.